Peningkatan Motivasi Belajar menggunakan Media Pembelajaran Berbasis Powerpoint dalam Pembelajaran Daring Tematik pada Siswa Kelas 3 SD Negeri 3 Bulukerto Kabupaten Wonogiri - Ary Listyaningsih; Heri Maria Zulfiati (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
Abstract: This research has purpose to give description about powerpoint based learning media.it is held because students’ motivation are low in pandemic term. In this situation, it needs learning media which can be used by synchronous. There are zoom and asycronous through wharsapp group. Student can study themselves. To collect data using questionary technique, equipment. To collect data is RPP. Teachers use powerpoint based learning media to improve students’ motivation. Powerpoint based learning media can be used by themselves. In powerpoint media have many quizzes which can increase students’ motivation Keywords: learning motivation, powepoint-based learning media, thematic online learning